Peningkatan Pola Berpikir Komputasi pada Siswa/i SMAK MATER DEI Melalui Bahasa Pemrograman Java dan Python - Rita Wiryasaputra; Albert Salomo; Nina Sevani; Seruni (Servirisma, 2022)
In this industrial era 4.0, the development of science, especially in the field of technology and information is growing rapidly. This requires every level of education in Indonesia to prepare students to move into the world of technology. Therefore, students must be equipped with an understanding of Computational Thinking (CT). CT is a method to train solving problems using several techniques in the field of computer science and informatics. With the application of CT, students are trained to think gradually, systematically, and creatively using computers and the internet. Through the application of this teaching, it’s hoped that it can advance the thinking of every student in Indonesia so that they can compete in the world of work later. Therefore, the Informatics Study Program, Faculty of Engineering and Computer Science, Krida Wacana Christian University, cooperates with SMAK Mater Dei by holding programming training in the form of extracurricular activities. This training takes place from 10 August 2021 to 9 November 2021. The training was held in 10 meetings which were divided into 3 phases, planning, implementation, and evaluation (finalization). The programming material includes Greenfoot IDE and Python programming language using several teaching methods. The measurement of student abilities will be tested using a pre-test and post-test model using several indicators. The assessment indicator used are the understanding of the algorithms and the ability to create simple programs using Greenfoot and Python. The training went well and students' understanding of Computational Thinking improved after the program was held.